1992
DOI: 10.1111/j.1699-0463.1992.tb04001.x
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus infection in Tanzania: a virological, epidemiological and clinical study among young children

Abstract: A. M. & Mhalu, F. Rotavirus infection in Tanzania: a virological, epidemiological and clinical study among young children. APMIS 100: 790-796, 1992. Rotavirus infection in the Dar es Salaam area of Tanzania was studied in 99 hospitalized children with acute diarrhoea and 99 hospitalized non-diarrhoea referents matched for sex and age. Of the diarrhoea cases 43.4% had rotavirus in the stools as opposed to 15.2% of the referents. The high carrier rate among the referents represents a serious risk of nosocomia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
6
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 16 publications
7
6
0
Order By: Relevance
“…The seasonal variation observed in the current study is further supported by findings from previous studies from the same region [36], [41]–[43]. Studies conducted during cool months of the year [41], [42] found high prevalence of rotavirus compared to studies conducted during hot months of the year [36], [43]. Understanding seasonal patterns of rotavirus will be useful when considering the appropriate timing of immunization booster programs in settings, which have reported poor efficacy of rotavirus vaccine and have demonstrated strong seasonality.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The seasonal variation observed in the current study is further supported by findings from previous studies from the same region [36], [41]–[43]. Studies conducted during cool months of the year [41], [42] found high prevalence of rotavirus compared to studies conducted during hot months of the year [36], [43]. Understanding seasonal patterns of rotavirus will be useful when considering the appropriate timing of immunization booster programs in settings, which have reported poor efficacy of rotavirus vaccine and have demonstrated strong seasonality.…”
Section: Discussionsupporting
confidence: 91%
“…Children with diarrhea were six times more likely to be infected with rotavirus than those without diarrhea. The study confirms findings from other studies twenty years ago in the same location and elsewhere [42], [44] indicating that rotavirus is still a major pathogen causing diarrhea in children in Tanzania. The presence of rotavirus among controls may represent reservoirs for transmission in the community.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar trends have been reported from many developing countries, namely India [56]; North African countries, such as Egypt [47] and Tunisia [50]; Central African countries, such as Malawi [48]; East African countries, such as Tanzania [44] and Kenya [45,46]; West African countries, such as Guinea-Bissau [51] and Nigeria [49]; and other Southern African countries, such as Zimbabwe [52].…”
Section: Discussionsupporting
confidence: 76%
“…The majority of previous studies in the RSA used diarrheal stool specimens obtained from hospitalized patients in urban and periurban areas [4,5,20,21,23,26,[41][42][43]; only 1 study addressed the HRV types in a rural community from a different province, namely Kwazulu-Natal [26]. Investigations into the HRV types circulating in other African countries, namely Tanzania [44], Kenya [45,46], Egypt [47], Malawi [48], Nigeria [49], Tunisia [50], and Guinea-Bissau [51], also focused predominantly on diarrheal specimens from urban and periurban communities, with limited studies in rural communities in Kenya [45,46], Zimbabwe [52], Ghana [53,54], and Gabon [55].…”
Section: Discussionmentioning
confidence: 99%